SECI-Based Knowledge Creation For Sustainable Agricultural And Aquaculture Communities In The Digital Age: A Systematic Literature Review And Future Research Agenda - Abdul Rajak Uar; Martani Huseini (Science and Education Journal (SICEDU), 2026)
This study presents a systematic literature review (SLR) examining the application, adaptation, and reinterpretation of the SECI model (Socialization, Externalization, Combination, Internalization) within the context of agricultural and aquaculture communities in the digital era. Drawing on 44 peer-reviewed articles published between 2016 and 2026, sourced from Scopus-indexed journals, this review addresses three research questions: (1) how the SECI model has been employed to explain community-based knowledge creation; (2) how SECI-based knowledge creation contributes to innovation and business sustainability; and (3) what economic, social, and environmental sustainability outcomes emerge from community-based knowledge creation, and what future research agenda can be developed for seaweed farming communities. The findings indicate that the SECI model remains a robust yet underutilized framework in agricultural and aquaculture settings, where tacit and explicit knowledge conversion drives collective learning, innovation, and sustainable development. Digital technologies function as enabling infrastructures that accelerate SECI cycles. This review identifies critical research gaps and proposes a future research agenda directed toward seaweed farming communities, a sector where knowledge creation mechanisms remain largely unexplored.